Short Communication: Mangrove area and mangrove carbon stock in the coastal city of Banda Aceh, Indonesia - WIRA DHARMA; ANGGI PRATIWI; SAIDA RASNOVI; DALIL SUTEKAD; ROSMADI FAUZI (Society for Indonesian Biodiversity, 2025)
Abstract. Dharma W, Pratiwi A, Rasnovi S, Sutekad D, Fauzi R. 2025. Short Communication: Mangrove area and mangrove carbon stock in the coastal city of Banda Aceh, Indonesia. Biodiversitas 26: 1582-1589. Climate change or global warming refers to the increase in Earth’s average surface temperature due to the greenhouse effect, with CO2 being one of the primary contributors. This has caused global temperatures to rise, significantly altering weather patterns, melting polar ice caps, and rising sea levels, which impacts the environment and public health. To mitigate carbon dioxide levels in the atmosphere, it is essential to enhance carbon absorption by utilizing mangrove vegetation. This study aims to assess the extent of mangrove areas in four sub-districts of Banda Aceh City and determine the associated mangrove carbon stocks. The research method employed the ArcGIS 10.8 software using Sentinel-2A satellite imagery (surface reflectance), accessed through the Google Earth Engine (GEE) platform, to calculate mangrove areas and carbon stocks. The results indicate that the Kuta Raja Sub-district has the largest mangrove area of 93.7531 ha, followed by Syiah Kuala (75.4098 ha), Kuta Alam (50.6548 ha), and Meuraxa (41.9272 ha). Regarding mangrove carbon stocks, the Kuta Alam Sub-district exhibits the highest carbon stock value in high-density class, ranging from 15.99 to 40.78 t C ha-1, followed by Kuta Raja (18.50-38.97 t C ha-1), Meuraxa (11.07-34.00 t C ha-1) and Syiah Kuala (9.71-28.43 t C ha-1).